Factors influencing green transformation efficiency in China's mineral resource-based cities: Method analysis based on IPAT-E and PLS-SEM. (1st January 2022) - Yin, Qing; Wang, Yadong; Xu, Zhehong; Wan, Kaidi; Wang, Delu
Abstract: China's mineral resource-based cities (MRBCs) face developmental difficulties, including environmental degradation, resource depletion, and economic growth. Therefore, there is an urgent need to explore factors affecting the green transformation efficiency of MRBC, which are expected to provide theoretical support and practical guidance for the formulation of scientific and effective transformation strategies. Based on the IPAT-E model and DEMATEL-ISM method, present study identifies and extracts four influencing factors: population, affluence, technology, and energy, and a multilevel systematic structural model of influencing factors was established. Meanwhile, the partial least squares method was employed to establish a structural equation model using data obtained from 110 MRBCs in China between 2009 and 2018. Factors influencing green transformation efficiency in different groups of MRBCs and the heterogeneity of these cities were analyzed. The results showed that affluence and energy had positive and negative direct and significant effects on transformation efficiency at the national level, respectively. At the same time, technology and population played significant positive roles through different intermediaries. Among them, the negative effect of energy was maximum, and the positive effect of technology was significant. From a regional perspective, the impact of affluence on the east, middle, west, and northeast was significant. The east had the greatest positive effect, whereas the west direction was negative. Furthermore, energy had a significant adverse effect on the central, western, and northeastern regions; however, its influence on the eastern region was not significant. The total indirect effects of technology on the east, middle, and northeast were significantly positive, but the impact on the west was not significant. Similarly, the indirect effect of the population was significant, although negative in the West. Based on city types, the influence of affluence on coal, oil, non-ferrous, and ferrous cities was significantly positive, among which the oil cities experienced the most significant influence. In contrast, the role of energy is significantly negative, as coal cities being the largest. The indirect effects of technology and population were also significantly positive. The former had the least impact on non-ferrous metal cities, while the latter had the greatest impact on oil cities. Therefore, the present study presents a multi-factor and systematic research framework to evaluate the factors influencing the green transformation efficiency of MRBCs, specifically evaluating the impact of various factors on China's MRBC green transformation efficiency for the first time; and proposes diverse strategies for different groups of MRBCs.